2017
DOI: 10.1186/s40810-017-0023-x
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear EEG biomarker profiles for autism and absence epilepsy

Abstract: Background: Although autism and epilepsy are considered to be different disorders, epileptiform EEG activity is common in people with autism even when overt seizures are not present. The relatively high comorbidity between autism and all epilepsy syndromes suggests the possibility of common underlying neurophysiological mechanisms. Although many different epilepsies may be comorbid with autism, absence epilepsy is a generalized epilepsy syndrome with seizures that appear as staring spells, with no motor signs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 58 publications
(86 reference statements)
1
55
0
3
Order By: Relevance
“…The changes in EEG complexity were also correlated with the improvement of catatonic symptoms and an increase of serum brain-derived neurotropic factor [12]. Although most studies showed decreased EEG complexity in individuals with ASD, an increased EEG complexity at rest has been noted in a study of older individuals with ASD [15], which showed that the EEG complexity of ASD was in between that of the control and individuals with absence seizures.…”
Section: Autism Spectrum Disordermentioning
confidence: 87%
See 2 more Smart Citations
“…The changes in EEG complexity were also correlated with the improvement of catatonic symptoms and an increase of serum brain-derived neurotropic factor [12]. Although most studies showed decreased EEG complexity in individuals with ASD, an increased EEG complexity at rest has been noted in a study of older individuals with ASD [15], which showed that the EEG complexity of ASD was in between that of the control and individuals with absence seizures.…”
Section: Autism Spectrum Disordermentioning
confidence: 87%
“…A recent study showed that the inter-ictal EEG complexity in children with CAE was significantly higher than the control over the frontal, occipital, temporal, and parietal areas [15]. In contrast, the reduction of EEG complexity in all channels during the seizure was noted in children with CAE [21].…”
Section: Childhood Absence Epilepsymentioning
confidence: 95%
See 1 more Smart Citation
“…[18][19][20]; and (ii) differentiating between mental health conditions with similar symptomatology, e.g. [21,22]. The majority of studies considered neuroimaging data (e.g., magnetic resonance imaging (MRI), electroencephalography (EEG), and positron emission tomography (PET)).…”
Section: Detection and Diagnosismentioning
confidence: 99%
“…Further, MRI data was used to diagnose patients with Alzheimer's disease and cognitive impairment, achieving reasonable accuracy [20]. In addition, ML has also been applied to the diagnosis of mental health conditions with similar symptomatology, for example differentiation of autism spectrum disorders and epilepsy using EEG data [21]. Research has also investigated the application of ML techniques to sensor, speech and video data to improve diagnosis of Alzheimer's disease [23], schizophrenia [24], and suicide ideation [25], achieving high accuracy.…”
Section: Detection and Diagnosismentioning
confidence: 99%